Sorafenib treatment is save and may affect survival of recurrent hepatocellular carcinoma after liver transplantation - Pfeiffenberger, Jan; Koschny, Ronald; Hoffmann, Katrin; Mehrabi, Arianeb; Schmitz, Anne; Radeleff, Boris; Stremmel, Wolfgang; Schemmer, Peter; Ganten, Tom M. (Langenbeck's archives of surgery, 2013)
Recurrent hepatocellular carcinoma (HCC) after liver transplantation (LT) is a rare but challenging condition. In most cases, the recurrent tumor is presented with extrahepatic spread. Therefore, systemic treatment with sorafenib has to be assessed. Because of a plethora of possible drug interactions, e.g., with immunosuppressant or anti-infective therapy, safety and feasibility of sorafenib treatment requires special attention.
Gesehen am 20.01.2022